Media and participation: a site of ideological-democratic struggle - Carpentier, Nico. (Online access: OAPEN Open Research Library (ORL), 2011)
"Participation has become fashionable again, but at the same time it has always played a crucial role in our contemporary societies, and it has been omnipresent in a surprisingly large number of societal fields. In the case of the media sphere, the present-day media conjuncture is now considered to be the most participatory ever, but media participation has had a long and intense history. To deal with these paradoxes, this book looks at participation as a structurally unstable concept and as the object of a political-ideological struggle that makes it oscillate between minimalist and maximalist versions."--Page 4 of cover.
https://katalog.adlr.link/Record/84-ocn729166877